The molecular regulation of oligodendrocyte development and CNS myelination by ECM proteins - Yamada, Momona; Iwase, Miho; Sasaki, Binri; Suzuki, Nobuharu (Frontiers in Cell and Developmental Biology, 2022)
Oligodendrocytes are myelin-forming cells in the central nervous system (CNS). The development of oligodendrocytes is regulated by a large number of molecules, including extracellular matrix (ECM) proteins that are relatively less characterized. Here, we review the molecular functions of the major ECM proteins in oligodendrocyte development and pathology. Among the ECM proteins, laminins are positive regulators in oligodendrocyte survival, differentiation, and/or myelination in the CNS. Conversely, fibronectin, tenascin-C, hyaluronan, and chondroitin sulfate proteoglycans suppress the differentiation and myelination. Tenascin-R shows either positive or negative functions in these activities. In addition, the extracellular domain of the transmembrane protein teneurin-4, which possesses the sequence homology with tenascins, promotes the differentiation of oligodendrocytes. The activities of these ECM proteins are exerted through binding to the cellular receptors and co-receptors, such as integrins and growth factor receptors, which induces the signaling to form the elaborated and functional structure of myelin. Further, the ECM proteins dynamically change their structures and functions at the pathological conditions as multiple sclerosis. The ECM proteins are a critical player to serve as a component of the microenvironment for oligodendrocytes in their development and pathology.